2017
DOI: 10.1007/s00038-017-1065-3
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic inequalities in health between Arabs and Jews in Israel: the relative contribution of individual-level factors and the living environment

Abstract: Arabs in Israel have poorer SRH than Jews. Polices to reduce this inequality should mainly focus on improving the SES and the living conditions of the Arabs, which might enhance health behaviors and well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
82
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 38 publications
5
82
0
Order By: Relevance
“…Discrimination has previously been documented as a barrier to smoking cessation in African Americans [ 44 ] and other minorities [ 17 ]. Some studies have suggested that social exclusion and discrimination of minority men are connected to fewer opportunities for higher education and less employment, which also increases stress, decreases attentiveness to healthy behaviors and encourages smoking [ 17 , 45 ], resulting in poor health [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Discrimination has previously been documented as a barrier to smoking cessation in African Americans [ 44 ] and other minorities [ 17 ]. Some studies have suggested that social exclusion and discrimination of minority men are connected to fewer opportunities for higher education and less employment, which also increases stress, decreases attentiveness to healthy behaviors and encourages smoking [ 17 , 45 ], resulting in poor health [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Arabs comprise one fifth of the population in Israel [ 24 ], but they have overall lower SES compared with their Jewish counterparts, higher poverty rates [ 48 ], lower education [ 49 ], and higher unemployment resulting from discriminatory institutional policies [ 50 ]. Health inequalities between them and the Jewish majority are related to gaps in living conditions [ 47 ]. Arab neighborhoods are characterized by high poverty and problems, including crime, violence and low collective efficacy [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations